Problem Solving as a creative means: a study on the lake area of Ramiro Ruediger Park in Blumenau/SC - Bertotti Junior, Vilmar Ibanor; Possamai, Janaína Poffo (Educação Matemática Debate, 2025)
This article aims to analyze the implications of the Teaching-Learning-Assessment methodology in Mathematics through Problem Solving to apply the trapezoidal method, developed by students based on their prior knowledge, in a context involving the calculation of the area of the lake in Ramiro Ruediger Park, in Blumenau/SC. To this end, the Problem Solving approach and its connection to creativity are discussed. This article presents an applied, qualitative, and action-research study, detailing the context, the structure of the practice, and the analysis of the investigated problem. The results indicate that this approach contributed to the development of students' autonomy, reasoning, argumentation, and creativity during the educational practice, advancing the understanding of mathematical concepts, with problem solving established as a pathway and guidance for learning.